The Role of the Religious Affairs Office in Reducing Early Marriage (Implementation of Law No. 16 of 2019 in Sidowayah Village, Pancur District, Rembang Regency) - Hata, Fuad; Kusmayadi, Rudy Catur Rohman (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
This research aims to examine the role of the Religious Affairs Office (KUA) and the effectiveness of the implementation of Law No. 16 of 2019 in reducing early marriage in Sidowayah Village. The research method used is descriptive qualitative with a phenomenological approach. Data was collected through in-depth interviews, participant observation, and documentation. The results showed that the KUA in Sidowayah Village plays an active role in socializing and edufuture bride and groomg the community about the dangers of early marriage and the provisions of Law No. 16 of 2019. The KUA's efforts have increased the community's understanding of the negative impacts of early marriage and children's rights. The implementation of Law No. 16 of 2019 has shown positive results by increasing public awareness of the minimum age for marriage. Education programs related to the dangers of early marriage and children's rights have shown positive results with indications of a decrease in the number of early marriages. However, there are several challenges in the implementation of this law, such as a lack of public awareness of the importance of complying with the law, strong cultural resistance in some environments, inconsistent law enforcement against violations of underage marriage, and social structures that support early marriage such as poverty and gender inequality. This research provides an overview of the role of KUA and the effectiveness of Law No. 16 of 2019 in efforts to reduce early marriage. Continuous and collaborative efforts from various parties, such as KUA, local government, and the community, are needed to address early marriage and achieve children's welfare. Keywords: Early marriage, Law no. 16 of 2019, KUA